Emergence of a chimeric globin pseudogene and increased Hemoglobin Oxygen Affinity Underlie the evolution of aquatic specializations in Sirenia - Signore, Anthony V.; Paijmans, Johanna L. A. (Dr.); Hofreiter, Michael (Prof.); Fago, Angela; Weber, Roy E.; Springer, Mark S.; Campbell, Kevin L. (Molecular Biology and Evolution, 2019)
As limits on O2 availability during submergence impose severe constraints on aerobic respiration, the oxygen binding globin proteins of marine mammals are expected to have evolved under strong evolutionary pressures during their land-to-sea transition. Here, we address this question for the order Sirenia by retrieving, annotating, and performing detailed selection analyses on the globin repertoire of the extinct Steller’s sea cow (Hydrodamalis gigas), dugong (Dugong dugon), and Florida manatee (Trichechus manatus latirostris) in relation to their closest living terrestrial relatives (elephants and hyraxes). These analyses indicate most loci experienced elevated nucleotide substitution rates during their transition to a fully aquatic lifestyle. While most of these genes evolved under neutrality or strong purifying selection, the rate of nonsynonymous/synonymous replacements increased in two genes (Hbz-T1 and Hba-T1) that encode the α-type chains of hemoglobin (Hb) during each stage of life. Notably, the relaxed evolution of Hba-T1 is temporally coupled with the emergence of a chimeric pseudogene (Hba-T2/Hbq-ps) that contributed to the tandemly linked Hba-T1 of stem sirenians via interparalog gene conversion. Functional tests on recombinant Hb proteins from extant and ancestral sirenians further revealed that the molecular remodeling of Hba-T1 coincided with increased Hb–O2 affinity in early sirenians. Available evidence suggests that this trait evolved to maximize O2 extraction from finite lung stores and suppress tissue O2 offloading, thereby facilitating the low metabolic intensities of extant sirenians. In contrast, the derived reduction in Hb–O2 affinity in (sub)Arctic Steller’s sea cows is consistent with fueling increased thermogenesis by these once colossal marine herbivores.